The Potentials of Sucen Tourism Activities to be Developed into a Smart Tourism Village in Bedulu Tourism Village, Bali - I Ketut Murdana; Ni Luh Putu Sri Widhiastuty (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
The objectives of this article were to explore, to identify and to present the tourism potencies owned by the Sucen Tourism Destination of Tegallinggah Tourism Village to be able to be developed as A Smart Tourism Village which was located at Bedulu Tourism Village in Gianyar Regency, Bali. The research method applied was Survey Research and the methods used for collecting data were observation and interviewed. The number of populationof the research were 30 people, and the sampling technique used was probability sampling technique where all the members of the population were given the same opportunity to be chosen as the sample of the research. The sampling technique used was Saturated Sampling Technique where all the members of the population were chosen as the samples of the research. In other words, the member of samples of the research were 30 people. The result of the research the tourism potencies owned by the sucen Tourism Village, such as the natural resources, the Human Recouses, excellent products and smart Tourism Village Potencies.